Análisis de factibilidad para mejorar la producción de arroz de las parcelas de los agricultores de la parroquia Yaguachi nuevo del cantón San Jacinto de Yaguachi de la provincia del Guayas - Sotomayor Cruz, Harry Fabián (2016)
This research focuses on a feasibility analysis to improve rice production plots of farmers in the new Yaguachi parish of Canton San Jacinto de Yaguachi in the province of Guayas, because the cultivation of rice in the sector Yaguachi new is vitally important for the impact that both socially and economically. Studies to increase the competitiveness of the rice production chain through innovation and technological development will result in greater welfare to farmers………